A cross sectional survey to assess the knowledge, attitude, practice about COVID-19 among bystanders of patients visiting OPD, AIIMS, New-Delhi, India - Chowdhary, Devanshi; Sharma, Ankita; Gopichandran, L. (International Journal Of Community Medicine And Public Health, 2021)
Background: According to WHO, the prevention and control of an epidemic and pandemic constitutes following preventive measures like hand washing, cough etiquette and dissemination of knowledge among other measures. In context to COVID-19, these measures have been proved to be very effective rendering various countries to be free of COVID-19. The knowledge, attitude and practice studies play an important role in assessing the societal readiness to accept behavioural changes, moreover they also determine baseline information to assess the actions to be taken to change the attitude and increase the knowledge of the people regarding the situation. Thus this study was undertaken to assess the knowledge, attitude and practice of the common public in India. Methods: A cross sectional survey was done among the attenders of patients visiting the cardiac/CTVS OPD during the month of June to July. A total of 200 patients attendants were enrolled in the study. Due to COVID-19 restrictions only 10 patients per day were enrolled. After obtaining informed consent an online questionnaire was sent to their mobile phones via electronic media and participants were requested to fill the questionnaire while waiting for the doctor’s visit. The knowledge, attitude and practice of the participants were assessed by a validated KAP survey questionnaire. Results: The participants had a good knowledge score. The mean knowledge score (minimum, maximum) among the population was 7.7±1.7 (0, 11) though the participants had a poor practice score of 2.3±1.01 (0, 4). The participants had a positive attitude regarding the preventive practices regarding COVID-19 and also a positive attitude towards health care workers. The mean attitude score was 21.3±3.5 (5, 25). A significant positive correlation (r=0.263) was found between knowledge and practice scores. A significant association was also found in between the age with attitude and practice scores, and also in between qualification with knowledge and total KAP score. Conclusions: The present study concludes that people have good knowledge regarding the various aspects of COVID-19, also there was positive correlation of knowledge with practice. Hence it is important to disseminate right knowledge regarding the pandemic COVID-19 so that general public performs the appropriate practices in order to keep themselves and their near ones safe. This study reflects the awareness of general public in the difficult time, as well as their helping attitude towards healthcare professionals in form of providing accommodation etc. Community awareness, participation and preparedness are key factors in achieving a good health for all.